Zum metasprachlichen Mehrwert der deutschen Kompositionsfuge - Roman Sadziński; Witold Sadziński (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
German composition fugues are inconspicuous and difficult to define, especially since their occurrence amounts to only about 30% of the total number of compositions. Nevertheless, a considerable number of the errors that occur are due to their incorrect use. Their linguistic status is just as bad. Mostly, contingent – possible, but not inherent – functions are mentioned: prosodic or that of signalling morpheme boundaries. In the present paper, the meta-linguistic added value of fugue oppositions is pointed out – preferably as indexing the language register contrasts between common and technical language with their relevant semantic differences.